Adsorptive remediation of cobalt oxide nanoparticles by magnetized α-cellulose fibers from waste paper biomass. (February 2019) - Kadam, Avinash; Saratale, Rijuta Ganesh; Shinde, Surendra; Yang, Jiwook; Hwang, Kyojung; Mistry, Bhupendra; Saratale, Ganesh Dattatraya; Lone, Saifullah; Kim, Dae-Youg; Sung, Jung-Suk; Ghodake, Gajanan
Graphical abstract: Highlights: Office paper waste (WP) extracted α-cellulose fibers (αCFs) was magnetized. M-WP-αCFs presented an effective adsorptive-remediation of CoO NPs from the water. The adsorption kinetics followed a pseudo-second-order rate model. Langmuir adsorption isotherm model was best fit to the experimental data. M-WP-αCFs can be effective for remediation of engineered NPs from the water. Abstract: Remediation of engineered-nanomaterials is an up-coming major environmental concern. This study demonstrates adsorptive-remediation of cobalt oxide nanoparticles (CoO NPs) from the water. The α-cellulose-fibers were extracted from waste-paper biomass (WP-αCFs) and magnetized with Fe3 O4 NPs (M-WP-αCFs). The XRD, FT-IR, and TGA were performed for detailed characterization of the newly developed bioadsorbent. The M-WP-αCFs was then applied for adsorptive remediation of CoO NPs. The adsorptive kinetics of CoO NPs adsorption onto the M-WP-αCFs reveals the pseudo-second-order model. The various adsorption isotherm studies revealed Langmuir is a best-fit isotherm. A prominently high adsorption capacity qm (1567 mg/g) corroborated extraordinary adsorptive potential of M-WP-αCFs. Furthermore, CoO NPs were adsorbed onto M-WP-αCFs were analyzed by the XPS, VSM, and TEM. Therefore, this study gave rise WP biomass extracted and rapidly-separable nano-biocomposite of 'M-WP-αCFs' with a high-capacity for CoO NPs remediation and can be further applied in remediation of several other engineered-nanomaterials.